Peer review of teaching in Australian higher education: a systematic review. Issue 2 (23rd February 2022) - Johnston, Alexandra L.; Baik, Chi; Chester, Andrea
ABSTRACT: Over recent decades, peer review of teaching has become an important mechanism for improving the quality of teaching in higher education. While there is considerable international research on peer review of teaching outcomes, these are not widely reported within Australian universities. This paper reports on a systematic review of published studies examining peer review of teaching characteristics that contribute to teaching development in Australian higher education. Following a search of peer reviewed literature published over three decades, 19 studies were included in the qualitative synthesis. A thematic synthesis revealed teaching development outcomes gained through peer review of teaching span factors at organisational ( N  = 16), program ( N  = 13) and individual ( N  = 4) levels. Organisational factors included disciplinary context, program sustainability, collegiality and leadership. Program factors included framework, program design, basis of participation, observation, feedback and reflective practice. Factors at the individual level included prior experience and participants' perceived development requirements. In addition to reporting on teaching development outcomes, some studies reported on enhanced student learning outcomes ( N  = 5). Improved reporting of program design in addition to validated tools to assess outcomes are required to better understand how peer review of teaching supports teaching development. The growth of peer review of teaching within Australian higher education presents an important opportunity to advance our understanding of practices influencing academic teaching development.